2020
DOI: 10.1016/j.engstruct.2020.110713
|View full text |Cite
|
Sign up to set email alerts
|

Theory and experimental verification of a resultant response-based method for assessing the critical seismic excitation direction of curved bridges

Abstract: Previous studies have shown that the seismic incidence angle imposes a non-negligible impact on the seismic performance of curved bridges. The computational efficiency of some current methods for determining the critical angle needs to be improved and their applicability in practical engineering projects remains to be examined. For this reason, a resultant response-based (RRB) method is developed herein for assessing the critical excitation direction of curved bridges. To validate the feasibility of this metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…More recently, researchers have focused on the seismic vulnerability assessment of curved bridges [17][18][19][20]. Some researchers recently developed some methods of identifying the critical seismic input angles for curved bridges and compared simulation results with shake table experiments [21,22]. These methods demonstrated good accuracy but took high computational costs.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, researchers have focused on the seismic vulnerability assessment of curved bridges [17][18][19][20]. Some researchers recently developed some methods of identifying the critical seismic input angles for curved bridges and compared simulation results with shake table experiments [21,22]. These methods demonstrated good accuracy but took high computational costs.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the responses of the bridge are not sensitive to the directionality of the input wave, and the maximum responses can be evaluated by the responses in longitudianl and transverse directions [15]. Feng et al (2020) developed a method to evaluate the maximum response of a curved bridge for the different seismic incidents. To verify the results, an experimental sample bridge was utilized, and the outcomes indicated that the method has acceptable accuracy in evaluating the input seismic angles [16].…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al (2020) developed a method to evaluate the maximum response of a curved bridge for the different seismic incidents. To verify the results, an experimental sample bridge was utilized, and the outcomes indicated that the method has acceptable accuracy in evaluating the input seismic angles [16]. Ramos-Sepulveda and Cabas, (2021) investigated the effect of site condition on the directionality of ground motions and the corresponding effects on the seismic response of structures.…”
Section: Introductionmentioning
confidence: 99%